Menuju Kesejahteraan Generasi Sandwich: Program Pendampingan dan Konseling - Taty Fauzi; Leo Ferdian Fauzi; Winda Lestari; Nurlena Nurlena; Rytha Petrossky (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This research is based on the phenomenon of the millennial generation who are traditionally trapped in life having to bear all the necessities of life for the previous generation such as parents, siblings and other family members. This condition causes various unrest that affects the sustainability of family life. Low financial conditions are a trigger for problems, but as children have responsibilities towards their parents. Community Service Activities aim to invite generation Z to hack and break the chain of life experienced by the millennial generation. The method of implementing community service uses a talk show model with discussion and sharing. The results of the implementation of Gen Z recognize the burdens and challenges faced and how to manage stress by having Stress management so that the basic thing as a key to not repeating it as the sandwich generation, students must prepare careful planning in managing finances by not behaving consumptively